2017
DOI: 10.1103/physrevb.96.115103
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of magnetic dynamics in αRuCl3

Abstract: We study the spin-wave excitations in α-RuCl3 by the spin-wave theory. Starting from the fiveorbital Hubbard model and the perturbation theory, we derive an effective isospin-1/2 model in the large Hubbard (U ) limit. Based on the energy-band structure calculated from the first-principle method, we find that the effective model can be further reduced to the K-Γ model containing a ferromagnetic nearest-neighbor (NN) Kitaev interaction (K) and a NN off-diagonal exchange interaction (Γ). With the spin-wave theory… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
107
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(126 citation statements)
references
References 50 publications
15
107
4
Order By: Relevance
“…40,67 Our result is in fair agreement with Kim et al and Li et al . As mentioned literature, the electronic and magnetic properties of bulk α-RuCl 3 can be described properly only when a proper Hubbard U term and SOC term is added.…”
Section: Model and Dft Simulation Detailssupporting
confidence: 93%
“…40,67 Our result is in fair agreement with Kim et al and Li et al . As mentioned literature, the electronic and magnetic properties of bulk α-RuCl 3 can be described properly only when a proper Hubbard U term and SOC term is added.…”
Section: Model and Dft Simulation Detailssupporting
confidence: 93%
“…Altogether, these experiments strongly suggest that α-RuCl 3 can be described by a generalized Kitaev-Heisenberg Hamiltonian [13,14], including off-diagonal and furtherrange interactions. Theory work leads to the same picture, whether the model is deduced from ab initio methods [12,[43][44][45][46][47][48][49], or from more phenomenological or ab initio inspired approaches [27,[50][51][52]. Unfortunately, these different works, as well as experimental fits [26,40], have led to a veritable zoo of proposed realistic spin Hamiltonian descriptions for α-RuCl 3 , and it's not currently clear which description is most accurate.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite intensive research efforts, controversy remains about the form of the basic interactions governing the physics of this material. Even the sign of the Kitaev interaction (the bonddependent anisotropic interaction responsible for Kitaev physics) is still under debate, with conflicting results from theoretical and experimental studies [5,6,[9][10][11][12][13][14][15]. The significance of the symmetric off-diagonal exchange interaction (referred to as the Γ term) is another contentious question [16][17][18].…”
mentioning
confidence: 99%
“…Early ab initio calculations [9] and fits to inelastic neutron scattering measurements [5,6] suggested an antiferromagnetic Kitaev interaction (K > 0). However, later calculations using the updated monoclinic crystal structure [4] instead suggested that the Kitaev term is ferromagnetic (K < 0) [10][11][12][13][14][15]. Although these scenarios can be distinguished by the direction of the ordered magnetic moment [22], to date, this information has not been experimentally available.…”
mentioning
confidence: 99%